A handbook on Sirach - Bullard, Roger Aubrey 1937-; Hatton, Howard A. 1929- (New York United Bible Societies, 2008)
Greek and Hebrew transliteration -- Translating Sirach (Ecclesiasticus) -- Translator's prologue -- Book one (1.1 23.27) -- Book two (24.1 42.14) -- Book three (42.15 50.24) -- Concluding matters (50.25 51.30)
Greek and Hebrew transliteration -- Translating Sirach (Ecclesiasticus) -- Translator's prologue -- Book one (1.1- 23.27) -- Book two (24.1- 42.14) -- Book three (42.15- 50.24) -- Concluding matters (50.25 51.30).
Includes bibliographical references (p. 1025-1030), glossary and index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Commentaries; Bible -- Translating; Kommentar